Pelatihan Manajemen Pemasaran Lembaga PAUD berbasis Web di TK Surakarta - Wahyuningsih, Siti; Rasmani, Upik Elok Endang; Nurjanah, Novita Eka; Jumiatmoko, Jumiatmoko; Zuhro, Nurul Shofiatin; Fitrianingtyas, Anjar; Winarji, Bambang (FKIP Universitas Sebelas Maret, 2023)
Early Childhood Education is an essential foundation to support further education. In reality, many institutions provide services to early childhood, both from the private sector and the government. However, only some of these institutions can compete amid competition for PAUD services in the digital era. Many institutions had to be merged and even closed because they did not have students, especially with the impact of covid 19, which made parents reluctant to send their students to PAUD. One of these phenomena experienced by institutions at LKMD Marsudisiwi Kindergarten in Surakarta and Aisyiah 20 Pajang Kindergarten in Surakarta is that it is undeniable that the impact of the COVID-19 pandemic and the lack of digital-based promotional management has reduced students entering the institution. Based on the results of the initial FGD between the service team and the TK LKMD Marsudisiwi Surakarta and TK Aisyiah 20 Pajang Surakarta, it was decided to hold a training in optimizing marketing management for web-based.